Caribbean Report 24-01-1991 - Whitehorne, Pat (anchor); Martin, Atherton (interviewee); Bennendijk, Chandra van (correspondent); Khan, Sharief (correspondent) (The British Broadcasting Corporation, 1991)
New negotiations between Guyana and the IMF for economic recovery support are expected to take place soon. All signs show that these talks would be tough since Guyana has not met last year’s targets. There is speculation that electricity charges will increase and the Guyana dollar will be devalued. In Suriname, the interim government is expected to announce the date of the next elections. Suriname has mounted a motivational campaign to encourage persons to vote and to ensure that the elections are conducted in a free and fair manner. Caribbean leaders are receiving increasing criticism for supporting the US by giving them the green light to commence war in Iraq. Mr. Atherton Martin, a Dominican and member of the Development GAP Organization in Washington, believes that the Caribbean has compromised its negotiating position with the United States. He adds that the Caribbean will be paying the price for fragmenting its bargaining position and this would affect the Caribbean in terms of receiving US aid. Martin adds that the Caribbean stands to lose out significantly because the US believes that it has the Caribbean it its back pocket. Britain’s Michael Robinson, whose parents are Jamaican, retained his Commonwealth Middleweight boxing title. He is hoping for a second shot and has set his sights on taking on Jamaican born, Chris Eubank.
1. Headlines (00:00-00:51)
2. New negotiations for economic recovery support between Guyana and the IMF are expected to take place soon (00:52-03:40)
3. Suriname’s interim government is expected to announce the date for new elections and motivational campaigns are apace to encourage persons to vote (03:41-06:20)
4. Caribbean leaders are receiving increasing criticism for supporting the US war initiative in Iraq (06:21-07:43)
Keywords: Guyana – economic aspects.; International economic relations – Caribbean area.; Financial Institutions, International.; International Monetary Fund.; Guyana - Politics and Government.; Elections – Suriname.; Political campaigns – Suriname.; Suriname – Politics and Government.; Caribbean area - Leadership.; War - Iraq.; Boxing – Tournaments – Caribbean area.; Caribbean Community -- leadership.; Robinson, Michael.; Caribbean leaders -- leadership.; Eubank, Chris.; Economic recovery support -- Caribbean area.; Development GAP Organization, Washington.